Exile and Nostalgia in Ancient Iraqi Literature - Dr. Saadoun (Journal of College of Education, 2025)
The study deals with the subject of alienation and nostalgia in ancient Iraqi literature. The first affects a person according to certain circumstances. Alienation may be spatial, represented by being away from family and homeland according to circumstances that may be beyond a person’s control, such as captivity, seeking a livelihood, or other circumstances. It may also be psychological, which is deeper and more intense than spatial alienation, as it is a feeling of isolation, separation, and loss of security and reassurance. As for nostalgia, it is more emphatic than alienation, as it is more extensive. There is hardly a person who does not yearn for a dear departed person, a place where he lived a good memory, a beautiful past he lived, or his country in its loftiness and glory. In this study, we will try to stand on these two terms and what is related to the feelings of the ancient Iraqi through his literary production that he left for us, which reflected his deep and complex human experience in a language that is not devoid of symbolism, allusion, and the beauty of the term.